Effect of 1-Methylcyclopropene (MCP)on Papaya Fruit Ripening - Ashariya Manenoi; Paull, R.E.
Papaya fruit during ripening exhibit a climacteric rise of respiration and ethylene production. Ethylene is involved in the initiation and coordination of ripening related-processes such as internal and skin color development, softening, and flavor and aroma development. Methylcyclopropene (MCP)is novel gas that acts as an inhibitor of ethylene action and delays the ripening in many climacteric fruit. The objective of this study was to characterize the physiological response of papaya fruit to MCP treatment. 'Rainbow' papaya color break fruit (<10
Keywords: SOFTENING; TEXTURE; RESPIRATION; ETHYLENE; TSS; CARICA PAPAYA